Leishmaniasis and HIV-infection – an actual problem? - T. N. Ermak; A. V. Kravchenko; V. I. Shahgil’dyan; E. N. Ponirovskij; N. Yu. Gankina (Журнал инфектологии, 2020)
The aim of the work is the clinical characteristics of all known cases of combined visceral leishmaniasis (VL) and HIV infection in the Russian Federation.Results. The article contains information on the problem of the combined course of HIV infection and leishmaniasis: a number of statistical and overview data in the world. A brief description of known cases of high blood pressure in patients with HIV infection in the Russian Federation, as well as a detailed description of the last patient diagnosed with VL in 2019 in Moscow. In all cases, the diagnosis of VL was difficult, which was due to clinical features and the lack of alertness of physicians in relation to VL. All but one of the patients contracted VL during their stay in Crimea.Conclusion. The authors point to the need for the formation of diagnostic alertness among doctors on this pathology, especially since with the expansion of tourist routes abroad in endemic countries, as well as in the Crimea, the relevance of this problem increases.